2004
DOI: 10.1590/s1516-14392004000400021
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical properties of alumina-zirconia composites for ceramic abutments

Abstract: The need for new materials to substitute injured or damaged parts of the human body has led scientists of different areas to investigate bioceramics since the 70's, when other materials in use started to show rejection problems. Ceramics show some advantages like being the material that best mimics the bone tissue, although present low toughness when compared with the metallic materials. As patients have become more and more demanding regarding esthetic and biocompatibility aspects of their dental restorations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
57
0
10

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(73 citation statements)
references
References 38 publications
6
57
0
10
Order By: Relevance
“…Such similarity was consistent with the behaviors discussed before as to the microstructure equality and density of the materials obtained by the two methods. It is observed that the values of elastic modulus were decreased as Y-TZP content increases in A/Y-TZP composites, being in accordance with reports in [172,178,179]. The obtained E values were close to prediction by rule of mixtures starting from the values corresponding to a slip casting alumina material with 99% of theoretical density (E = 400 GPa, v = 0.22) and those corresponding to Y-TZP (E = 210 GPa, v = 0.31), demonstrated the high density and low defects number in materials.…”
Section: Elastic Modulussupporting
confidence: 91%
See 1 more Smart Citation
“…Such similarity was consistent with the behaviors discussed before as to the microstructure equality and density of the materials obtained by the two methods. It is observed that the values of elastic modulus were decreased as Y-TZP content increases in A/Y-TZP composites, being in accordance with reports in [172,178,179]. The obtained E values were close to prediction by rule of mixtures starting from the values corresponding to a slip casting alumina material with 99% of theoretical density (E = 400 GPa, v = 0.22) and those corresponding to Y-TZP (E = 210 GPa, v = 0.31), demonstrated the high density and low defects number in materials.…”
Section: Elastic Modulussupporting
confidence: 91%
“…Narrow grain size distributions were observed for both phases in each composite. It was clear that the fine and bimodal distribution of particle sizes allowed the most efficient fulfilling of the matrix for uniaxially pressing, promoting better densification of the powders [172].…”
Section: Density and Microstructurementioning
confidence: 99%
“…The applied load was 19.614 N for 6 second over polished surface. The values of microhardness were calculated from the following equation [8]:…”
Section: Microhardness Of the Composites Was Measured By Vickers Indementioning
confidence: 99%
“…Composites with higher density and lower porosity offer better mechanical properties [8]. The presence of porosity can reduce fracture toughness by the reduction of the resistant area by the effect of stress concentration in the pores.…”
Section: Density and Porositymentioning
confidence: 99%
“…Повышенная водопотребность мелких песков отрицательно сказывается на показателях прочности и плотности что приводит к формированию проницаемой структуры. Полученные данные хорошо согласуются с подобными исследованиями проводимыми в России и за рубежом [7][8][9][10].…”
Section: Barcelona Venezuela 51unclassified